Návrh převodů HPV - Martinát, Antonín (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Tato diplomová práce se zabývá návrhem převodového ústrojí vozidla poháněného lidskou silou. Nejprve je zde krátká rešeršní část používaných převodových ústrojí, poté následuje vlastní konstrukční návrh a pevnostní výpočet vybraných dílů. K práci je přiložena výkresová dokumentace.

This diploma thesis concerns the design proposal for a bicycle gearbox powered by human force. The first part summarizes the existing solutions. The second part includes the proposal of the new design, together with the calculation of the strength for selected parts. Attached are the drawings documenting the findings.
Transmission of HPV
Keywords: HPV; vozidlo poháněné lidskou silou; převodové ústrojí; ozubené kolo; HPV; human powered vehicle; gearbox; gear